2015
DOI: 10.7863/ultra.15.03039
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Assessment of Sentinel Lymph Nodes in Breast Cancer Using Shear Wave Elastography

Abstract: Shear wave elastography can be used with grayscale sonography for evaluation of cases to decide on needle biopsy sampling. However, it cannot be used as a replacement for fine-needle aspiration or SLN dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 27 publications
5
22
1
Order By: Relevance
“…In the European Federation of Societies for Ultrasound in Medicine and Biology and World Federation for Ultrasound in Medicine and Biology guidelines for the breast, both strain elastography and SWE were recommended to help in the diagnosis of breast lesions . Meanwhile, two studies investigating sentinel lymph nodes of breast cancer concluded that SWE was not useful since it was difficult to detect micrometastasis similar to our data on MM lesions. In the present study, the elastographic properties were assessed in only one plane, and the percentages of hard tissue were not assessed for the whole lymph node volume, which is a limitation of this study.…”
Section: Discussionsupporting
confidence: 72%
“…In the European Federation of Societies for Ultrasound in Medicine and Biology and World Federation for Ultrasound in Medicine and Biology guidelines for the breast, both strain elastography and SWE were recommended to help in the diagnosis of breast lesions . Meanwhile, two studies investigating sentinel lymph nodes of breast cancer concluded that SWE was not useful since it was difficult to detect micrometastasis similar to our data on MM lesions. In the present study, the elastographic properties were assessed in only one plane, and the percentages of hard tissue were not assessed for the whole lymph node volume, which is a limitation of this study.…”
Section: Discussionsupporting
confidence: 72%
“…Higher SWV of breast cancer showed higher possibility of ALN metastasis 18,19 . However, the performance of 2D-SWE depends on the placement of regions of interest (ROI) and the AUC was only 0.759 for the prediction of ALN status 17,20 . Therefore, only SWE images of breast cancer might be insufficient to evaluate ALN status accurately.…”
mentioning
confidence: 99%
“…[5,6]. These features can provide valuable information for the characterization of abnormal ALNs [7][8][9], and help identify lymph nodes suitable for needle biopsy [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Collagen is a very stiff material with an elastic modulus of 37.7 to 42.4-GPa [21], which may change the mechanical properties of metastatic ALNs. Normal ALNs have been reported to have an elastic modulus of 2.4 to 38.9-kPa [13,16].…”
Section: Introductionmentioning
confidence: 99%